Odpowiedzi

  • Roma
  • Community Manager
2010-02-17T10:09:31+01:00
A) 3 √5 - 2 + √5 - 2 = 4√5 - 4

b) 4∛2 - 5(2∛2 + 1 ) = 4∛2 - 10∛2 - 5 = - 6∛2 - 5

c) √72 - √32 - 3√8 = √36*2 - √16*2 - 3√4*2 = 6√2 - 4√2 - 3*2√2 = 6√2 - 4√2 - 6√2 = - 4√2

d) 2∛24+ ½(∛192 - ∛375) = 2∛8*3 + ½(∛64*3 - ∛125*3) = 2*2∛3 + ½(4∛3 - 5∛3) = 4∛3 + ½(- ∛3) = 4∛3 - ½∛3 = 3½∛3

e) 3√5² - 5⁻² = 3*5 - ¹/₅² = 15 - ¹/₂₅ = 14²⁴/₂₅
7 3 7
Najlepsza Odpowiedź!
2010-02-17T10:13:43+01:00
A) 3 √5 - 2 + √5 - 2 = 4√5 - 4= 4(√5 - 1)

b) 4∛2 - 5(2∛2 + 1 ) = 4∛2 - 10∛2 + 5 = -6∛2 + 5

c) √72 - √32 - 3√8 = √36×2 - √16×2 - 3 √4×2 = 6√2 - 4√2 - 6√2 = -4√2

d) 2∛24+ ½( ∛192-∛375) = 2∛8×3 + ½ ∛64×3 - ½ ∛125×3 = 4∛3 + 2∛3 - 2,5∛3 = 3,5 ∛3

e) 3√5² - 5⁻² = 3√25 - (⅕)² = 15 - 1/25 = 14 24/25
7 3 7